Pengaruh Rasio Umpan Terhadap Produksi Bio-Oil Dari Co-Pyrolysis¬ Tandan Kosong Kelapa Sawit Dan Low-Density Polyethyelene - Nanda, Widia Rizki; Sunarno, Sunarno; Zahrina, Ida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bio-oil is a dark brown liquid consisting of aliphatic, aromatic, and heterocyclic compounds which have the potential to be liquid fuels. Bio-oil can be produced from a mixture of biomass and synthetic polymers through the co-pyrolysis process. Copyrolysis is a pyrolysis process that involves two or more different materials as a feedstocks. Potential feedstocks for the production of bio-oil are oil palm empty fruit bunches (OPEFB) and low-density polyethylene (LDPE). The purposes of this study were to determine the effect of feed ratio on bio-oil yield, and characterize the physical properties of bio-oil. The co-pyrolysis process using OPEFB and LDPE as feedstocks, the feed ratio (OPEFB/LDPE) was varied in 100/0, 75/25, 50/50 and 25/75 at temperature was 400°C. The results of this study showed that the best bio-oil yield obtained at feed ratio of 25% OPEFB / 75% LDPE was 63.2%. The characteristics of physical properties such as density, viscosity, acidity and heating value of the best biooil were 0.838 g/ml, 3.63 cSt, 3.81 and 35.3 MJ/kg. The results of this study indicate that the pyrolysis process between OPEFB and LDPE has a positive synergistic effect that increases hydrocarbon content and reduces phenol content in bio-oil. Key words: bio-oil, co-pyrolysis, LDPE, liquid fuels, OPEFB